The Importance of Early Childhood Education in The Family As Forming The Basis of Muslim Personality - Nurul masruroh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2017)
The early age education in the family is very important as basic to form Moslem personality. The parents should understand and realize that education is not started when the children come in to formal institution. Really, education is given to children since they were born and did not have to give in the formal institution only. Education of early of age child in the family is the first and primary for the next child growth. Because a lot of child’s time is finished at the family with their parents. Role of the parent as educator is needed, because they have related with process, goal, and result of child education in the family.There are three problems in this research, first, how is the education of early age of children in the family according to Islam, second, how the concept to form the Moslem personality, and third, how is the urgent of education of early age of children as basic to make Moslem personality.Kind of research did by writer is library research, The steps in this research are to fix the general idea of research, to look for information to support the topic, to clear the research focus and materials organizing, to look for and to find reading material (articles, journals, references, published documents, manuscript, etc), to reorganize and making research notes, to review and to rich the reading materials, to reorganize the notes, and starting to write. The approaches that used in this research are psychological and sociological approach. Analyses method used in this research is qualitative descriptive, inductive and deductive think method.Based on the research result, so is concluded: first, that the education of early age of the children is continued on 0-7 years old, on the 0-7 years old the children experiences the important growth viewed from various point of view. Moreover, on this age the most important periods all of the human living stretches. So it is called as critical period to children growth for the next period. Education of the golden age is had to do stately by various methods that exact to the children. Second, The Moslem personality is not the instant and permanent thing, but it is a dynamic and by process that done since early age. The education of early age of the children in the family is very important to base Moslem personality. Because. Some one’s personality is formed by internal and external factors, one of them is education that is received, especially informal or family education on the early age. Third, the personality will be formed by education that the truth is habit process. The habit that has given since early age will be formed children character, and finally will be personality of the children. If since on the early age the children are educated according to Islamic laws, so the children will have the Moslem personality.